Ctk1 promotes dissociation of basal transcription factors from elongating RNA polymerase II - Ahn, Seong Hoon (Nature Publishing Group, 2009)
As RNA polymerase II (RNApII) transitions from initiation to elongation, Mediator and the basal transcription factors TFIID, TFIIA, TFIIH, and TFIIE remain at the promoter as part of a scaffold complex, whereas TFIIB and TFIIF dissociate. The yeast Ctk1 kinase associates with elongation complexes and phosphorylates serine 2 in the YSPTSPS repeats of the Rpb1 C-terminal domain, a modification that couples transcription to mRNA 3′-end processing. The higher eukaryotic kinase Cdk9 not only performs a similar function, but also functions at the 5′-end of genes in the transition from initiation to elongation. In strains lacking Ctk1, many basal transcription factors cross-link throughout transcribed regions, apparently remaining associated with RNApII until it terminates. Consistent with this observation, preinitiation complexes formed on immobilized templates with transcription extracts lacking Ctk1 leave lower levels of the scaffold complex behind after escape. Taken together, these results suggest that Ctk1 is necessary for the release of RNApII from basal transcription factors. Interestingly, this function of Ctk1 is independent of its kinase activity, suggesting a structural function of the protein.